Comparison of vascular and neurological parameters between diabetic subjects without diabetic foot ulceration or amputation and those with either foot ulceration or a lower extremity amputation : a pilot study - Rheeder, Paul (University of Pretoria, 2013)
Dissertation (MSc (Clinical Epidemiology))--University of Pretoria, 2007.